Development of an E-Reporting Application for Road Damage in Palembang at the Department of Public Works and Housing (PUPR) - Endi Andika (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2023)
Community participation plays a crucial role in supporting the government in developing and maintaining public infrastructure. One of the common public complaints in Palembang City concerns damaged roads, which significantly affect transportation and safety. At present, reports of road damage are typically submitted through social media, creating inefficiencies because the Department of Public Works and Housing (PUPR) of Palembang City cannot effectively filter or categorize these reports. As a result, duplicate submissions and unverified data often occur, slowing the response process. This study aims to develop a mobile-based E-Reporting application for road damage in Palembang City using the Extreme Programming (XP) method. The application allows the public to report damaged roads through a smartphone interface, while the PUPR Office can manage and verify the reports through a web-based dashboard. The XP method provides an adaptive, iterative development process that responds quickly to user requirements. The resulting system successfully enables the collection, verification, and processing of road damage reports. Through this platform, the public can actively participate in infrastructure monitoring, while the PUPR Office can improve the efficiency, transparency, and accountability of road maintenance management in Palembang City.